rdlc 2022
DOI: 10.7764/rdlc.21.3.506
|View full text |Cite
|
Sign up to set email alerts
|

Flexural behavior of concrete beams reinforced with glass fiber reinforced polymer and steel bars

Abstract: In this study, a comparative experimental analysis is performed between steel-reinforced concrete beams, which are dimensioned based on NBR 6118 (2014), and beams reinforced with glass fiber-reinforced polymer (GFRP) rebar, which are dimensioned based on ACI 440.1R (2015) after being subjected to a four-point bending test. The beams are dimensioned to resist the same force and to satisfy the service limit state (SLS). Results show that the two groups of beams exhibit similar vertical displacement behaviors unt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…The findings of the study showed that concrete beams containing M-sand and reinforced with GFRP possessed a 12% higher load than corresponding beams with river sand and reinforced with steel, although the lower modulus of elasticity of the GFRP bars affected the post-cracking stiffness. Farias et al [23] compared the flexural behavior of GFRP-reinforced concrete beams with corresponding concrete beams containing a steel area equal to 40% of the fiber glass area. The results of the study showed that the beams with GFRP bars possessed a 64% higher flexural resistance and exhibited less deflection compared with those containing steel bars.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The findings of the study showed that concrete beams containing M-sand and reinforced with GFRP possessed a 12% higher load than corresponding beams with river sand and reinforced with steel, although the lower modulus of elasticity of the GFRP bars affected the post-cracking stiffness. Farias et al [23] compared the flexural behavior of GFRP-reinforced concrete beams with corresponding concrete beams containing a steel area equal to 40% of the fiber glass area. The results of the study showed that the beams with GFRP bars possessed a 64% higher flexural resistance and exhibited less deflection compared with those containing steel bars.…”
Section: Literature Reviewmentioning
confidence: 99%